Model Epistemologis Penyusunan Proposal Penelitian Tafsir bagi Pengembangan Riset Ilmu Al-Qur’an - Muhammad Riski Situmorang; Silmi Alawiyah Siregar; Farid Adnir (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2026)
The problems in preparing an interpretation research proposal reveal the tension between the classical epistemological framework and contemporary methodological demands, which often leads to unclear scientific foundations, inconsistent approaches, and weak scientific argumentation. The purpose of this study is to formulate a systematic epistemological model as a conceptual basis for designing an interpretation research proposal that is coherent, analytical, and relevant to the development of Qur’anic science. A qualitative approach based on a literature study is used, through critical reading of the interpretation literature, research methodology, and epistemological theory, with an epistemological-critical orientation. The results of the study show four main findings: first, identification of epistemological foundations that include sources of knowledge, validity of interpretation, and ontological framework of the text; second, mapping of methodological problems in the form of reductionism of approach, inconsistency between problem formulation and method, and minimal integration of context; third, formulation of the ideal structure of the proposal that includes coherence between the background, problem formulation, objectives, theoretical framework, method, and scientific contribution; fourth, epistemological integration emphasizes the dialectical relationship between text, interpreter, and context in the research process. Scientific implications confirm this model’s contribution to improving the quality of interpretive research proposals, making them more systematic, critical, and contextual, thereby strengthening the sustainable development of Qur’anic research.